Surrogate-Based Design Optimization of Multi-Band Antenna - Belen, Aysu; Tari, Ozlem; Mahouti, Peyman; Belen, Mehmet A.; Caliskan, Alper (RIVER PUBLISHERS, 2022)
In this work, design optimization process of a multi-band antenna via the use of artificial neural network (ANN) based surrogate model and meta-heuristic optimizers are studied. For this mean, first, by using Latin-Hyper cube sampling method, a data set based on 3D full wave electromagnetic (EM) simulator is generated to train an ANN-based model. By using the ANNbased surrogate model and a meta-heuristic optimizer invasive weed optimization (IWO), design optimization of a multi-band antenna for (1) 2.4-3.6 GHz for ISM, LTE, and 5G sub-frequencies, and (2) 9-10 GHz for X-band applications is aimed. The obtained results are compared with the measured and simulated results of 3D EM simulation tool. Results show that the proposed methodology provides a computationally efficient design optimization process for design optimization of multiband antennas.
Keywords: Artificial Neural Network (ANN); multiband antenna; optimization; surrogate modeling; INVASIVE WEED OPTIMIZATION; YIELD ESTIMATION; COMPACT; FILTER; Engineering; Telecommunications